PENERAPAN PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM) PADA USAHA KECIL MENENGAH (UKM) STUDI KASUS PADA TOKO Y.O.K VAPE (ROKOK ELEKTRIK) - B51111158, REZA PANGESTU (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
This research aims to implement SAK EMKM on the arrangement of financial report of Y.O.K Vape which works in electric cigarette trading in order to earn benefits and to provide jobs, which has not implemented SAK EMKM in the precentation of financial report and to discover factors that become problems in Y.O.K Vape shop Pontianak in implementing SAK EMKM.The tools of analysis used are qualitative analysis which used SAK EMKM in composing the financial report, and interview to find the problems on Y.O.K Vape shop Pontianak which in fact has not implemented SAK EMKM.The result of this research shows that Y.O.K Vape shop Pontianak is able to implement the SAK EMKM on its financial report altough in a simple form. Besides, the researcher is able to know problems that overcomed by Y.O.K Vape shop Pontianak which has not implemented the SAK EMKM since the accountant has not known the SAK EMKM and it has its own simple financial report to be understood by its employees.Â Keywords : SAK EMKM, financial report, trading company